Strength Gains by Motor Imagery with Different Ratios of Physical to Mental Practice - Reiser, Mathias; Büsch, Dirk; Munzert, Jörn (Frontiers in Psychology, 2011)
The purpose of this training study was to determine the magnitude of strength gains following a high-intensity resistance training (i.e., improvement of neuromuscular coordination) that can be achieved by imagery of the respective muscle contraction (IMC training). Prior to the experimental intervention, subjects completed a 4-week standardized strength training program. 3 groups with different combinations of real (MVC) and mental (IMC) strength training (M75, M50, M25; numbers indicate percentages of mental trials) were compared to a MVC-only training group (M0) and a control condition without strength training (CO). Training sessions (altogether 12) consisted of four sets of two maximal 5-s isometric contractions with 10 s rest between sets of either MVC or IMC training. Task-specific effects of IMC training were tested in four strength exercises commonly used in practical settings (bench pressing, leg pressing, triceps extension, and calf raising). Maximum isometric voluntary contraction force (MVC) was measured before and after the experimental training intervention and again 1 week after cessation of the program. IMC groups (M25, M50, M75) showed slightly smaller increases in MVC (3.0% to 4.2%) than M0 (5.1%), but significantly stronger improvements than CO (-0.2%). Compared to further strength gains in M0 after 1 week (9.4% altogether), IMC groups showed no "delayed" improvement, but the attained training effects remained stable. It is concluded that high-intensity strength training sessions can be partly replaced by IMC training sessions without any considerable reduction of strength gains.